Children's playground accessibility in the North of Portugal - Pereira, Beatriz Oliveira (2004)
With the growing significance of sedentary activities, such as television-watching, playgrounds remain important leisure facilities for children, since physical play activities have an important role in supporting children's motor, social and emotional development. When children have the opportunity to play in a playground they are promoting healthy lifestyles. In Portugal children are required to attend school until the age of 16 years and are provided with education, which is regulated by national government standards, but in regard to leisure opportunities, there is considerable inequality of provision from locality to locality. Seeking to promote the principles of play and health in the open air, a project was developed to discover the pattern of provision of children's playgrounds in different regions of the North of Portugal and to examine their physical characteristics. A questionnaire was developed and sent to Town Halls, seeking information on playground provision in each district and on the characteristics of the equipment provided in the playgrounds. This study includes four sub-regions – Ave, Cávado, Minho-Lima, Alto Trás-os-Montes – that include 38 districts. The north region of Portugal has 21.194 km2 and over 3.600.000 inhabitants and is one of the regions in Europe with youngest population. The results of the survey are presented in this paper. It was found that almost half of the districts surveyed provided less than 5 playgrounds in their area. Playgrounds are located mostly in areas without heavy traffic and the majority of playgrounds have minimal equipment - typically four or less items. Children in general therefore have few opportunities to play in playgrounds because of lack of provision and have very few opportunities to choose the activities they like to engage in because of the lack of attractive equipment. The paper discusses the implications of these findings for policy-makers in the region.